Evaluation of Asset Management Policies in Increasing Learning Quality in the Gorontalo State Junior High School - Yanti Aneta; Husin Ali (AIBPM Publisher, 2018)
The purpose of this study was to determine the evaluation of asset management policies in improving the quality of learning: (1) infrastructure facilities planning in Gorontalo City Public Middle School, (2) procurement of infrastructure in Gorontalo City Public Middle School, (3) infrastructure maintenance in Gorontalo City Public Middle School, (4) removal of infrastructure facilities in Gorontalo City State Middle School. The method used in this study is descriptive method with the Goal Attaiment evaluation model covering aspects of planning, procurement, maintenance and deletion. Data sources in this study are primary data sources and secondary data. Data was collected through observation, interviews, documentation and questionnaires. The findings of the study were first, the results of the evaluation of infrastructure facilities planning in Gorontalo City State Middle School were in the high category. Secondly, the results of the evaluation of the infrastructure procurement component in Gorontalo City Public Middle School are in the high category. Third, the results of the evaluation of the infrastructure maintenance component in Gorontalo City State Middle School are in the high category. Fourth, the results of the evaluation of the component of infrastructure deletion in Gorontalo City Public Middle School are in the high category. The conclusions of this study are (1) evaluation of infrastructure infrastructure planning components in Gorontalo City Public Middle School focused on aspects: land acquisition planning, building procurement planning, building construction planning, furniture procurement and educational equipment planning. (2) The results of the evaluation of the infrastructure procurement component in Gorontalo City State Junior High School are carried out through aspects: regulations and procurement policies, infrastructure procurement procedures, quality of procurement of facilities and infrastructure, and quantity of infrastructure. (3) The results of the evaluation of the infrastructure maintenance component in Gorontalo City State Junior High School are carried out through aspects of: maintenance programs, and the use of infrastructure. (4) The results of the evaluation of the components of infrastructure deletion in Gorontalo City State Junior High School are carried out through aspects of: financing, security and the release of infrastructure Keywords: Evaluation of asset management policies, infrastructure